E-COMMERCE IN UZBEKISTAN - Ahmadov, Og‘abek Otabek o‘g‘li; Otavullaev, Suxrob Sa’dulla o‘g‘li (Educational Research in Universal Sciences, 2023)
Nowadays, the internet and technology are developing rapidly. online sales are increasing their share in traditional sales day by day. At the same time, e-commerce is rapidly developing in our country, Uzbekistan, and it is entering all areas. People feel uncomfortable and time consuming for going crowded markets. So, E-Shopping is a boon as it saves lot of time. Online shopping is a process whereby consumers directly buy goods, services etc. from a seller without an intermediary service over the Internet. Shoppers can visit web stores from the comfort of their house and shop as by sitting in front of the computer. Online stores are usually available 24 hours a day and many consumers have internet access both at work and at home.